Assessing Critical Criteria for Historical Archeological Buildings in Iraq - Abdullah, O. H.; Hatem, W. A. (Engineering, Technology & Applied Science Research, 2022)
-This research was conducted to identify and evaluate the relative importance of the criteria in an archaeological building. Open and closed questionnaires were used and interviews with experts and specialists from many ministries and governorates were conducted to identify the most important criteria. The aim determines what factors influence historic archaeological building success, and which criteria should be used to determine the best response. The data were analyzed with the SPSS V25 program using the Relative Importance Index (RII) method to determine the relative importance of the considered 15 variables. RII allows the identification of the most important criteria based on responses from participants, and it is a useful tool for prioritizing indicators rated on Likert-type scales. The data were analyzed using a formula from a previous study's relative index analysis method. Providing information or a database of historic old buildings ranked first with RII = 92%, and providing information on the changes taking place in old buildings ranked second with RII = 88%.